THE ROLE OF TEACHERS IN THE FORMATION OF CIVIC CULTURE AND OPPORTUNITIES TO IMPROVE CIVIC CULTURE AMONG YOUNG PEOPLE - Sobirov F. X. (Galaxy International Interdisciplinary Research Journal, 2021)
This article substantiates the essence and content of civil culture as an important component of the entire harmoniously developed generation from a scientific and theoretical point of view. As well as revealing some features of civil society, the models of civil culture of the younger generation of civil society are presented.